The Absence of the African‐American Owned Business: An Analysis of the Dynamics of Self‐Employment - Fairlie, Robert W. (Journal of Labor Economics, 1999)
Estimates from the Panel Study of Income Dynamics indicate that African-American men are one-third as likely to be self-employed as white men. The large discrepancy is due to a black transition rate into self-employment that is approximately one-half the white rate and a black transition rate out of self-employment that is twice the white rate. Using a new variation of the Blinder-Oaxaca decomposition technique, the author finds that racial differences in asset levels and probabilities of having self-employed fathers explain a large part of the gap in the entry rate, but almost none of the gap in the exit rate. Copyright 1999 by University of Chicago Press.